Inhibition of IL-12 production by 1,25-dihydroxyvitamin D3. Involvement of NF-kappaB downregulation in transcriptional repression of the p40 gene. - D'Ambrosio, D (1998)
Interleukin 12 (IL-12), produced by myelomonocytic cells, plays a pivotal role in the development of T helper 1 (Th1) cells, which are involved in the pathogenesis of chronic inflammatory autoimmune disorders. 1,25-Dihydroxyvitamin D3 [1,25(OH)2D3] inhibits IL-12 production by activated macrophages and dendritic cells, thus providing a novel interpretation to its immunosuppressive properties. 1,25(OH)2D3 significantly inhibits mRNA expression for both IL-12 p35 and p40 subunits acting at the transcriptional level. The effect of 1,25(OH)2D3 on p40 promoter activation was analyzed by cotransfecting monocytic RAW264.7 cells with p40 promoter/reporter constructs and expression vectors for vitamin D3 receptor (VDR) and/or retinoid X receptor (RXRalpha). We observed transcriptional repression of the p40 gene by 1,25(OH)2D3, which required coexpression of VDR with RXR and an intact VDR DNA-binding domain. The repressive effect maps to a region in the p40 promoter containing a binding site for NF-kappaB (p40-kappaB). Deletion of the p40-kappaB site abrogates part of the inhibitory effect on the p40 promoter, confirming the functional relevance of this site. Activation of monocytic THP-1 cells in the presence of 1,25(OH)2D3 results in reduced binding to the p40-kappaB site. Thus, 1,25(OH)2D3 may negatively regulate IL-12 production by downregulation of NF-kappaB activation and binding to the p40-kappaB sequence.